Good Knowledge Makes Good Behavior In Giving Vitamin A To Toodler - Anik Kurniawati; Mey Lely Setyaningrum; Sumantri Sumantri (Jurnal Kebidanan dan Kesehatan Tradisional, 2021)
Background: Vitamin A is one of the important nutrients that is fat-soluble and stored in the liver, cannot be made by the body so it must be met from the outside. Data from East Java Provincial Health Office note that the scope toddlers who received vitamin A capsules in 2019 reached 90.80% and has met the 2019 target of 90.8%. Meanwhile, the coverage of giving vitamin A capsules in Ngawi Regency is 75.9% of the target of 90.80% in 2019. The purpose of the study were to identify the characteristics of respondents based on age, education and occupation, to describe the mother's knowledge about vitamin A capsules in toddlers, to describe the attitudes of mothers about vitamin A capsules to toddlers. Methods: Descriptive quantitative research methods with a survey approach. The sampling technique was total sampling with a sample size of 60 mothers with toddlers aged 6-59 months at the Posyandu I Kartoharjo Village, Ngawi in 2021. The data analysis technique used was descriptive statistics. Results: The characteristics of the respondents based on the majority age 21-35 years (73%), based on the education of the majority of High School (42%), based on the occupation of the majority of housewives (78%), the description of the mother's knowledge about vitamin A capsules was mostly good (58 %), the majority of mothers' attitudes about vitamin A capsules support (96%). Conclusion: The reseacrh measurement knowledge and attitudes of mothers about vitamin A capsules in toddlers during the covid-19 pandemic at the Posyandu I Kartoharjo Village, Ngawi is good. However, there is still knowledge and attitudes that are lacking and unsupportive, during the pandemic covid 19, it is hoped that efforts to increase the knowledge and attitudes of respondents about vitamin A.